The Relationship of Employee Engagement, Quality of Work Life and Organizational Commitment with Turnover Intention Nurse from Unand Padang Hospital in 2023 - Engga Lift Irwanto; Rizanda Machmud; Yuniar Lestari (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This research was conducted with the aim of analyzing the relationship between the implementation of employee engagement, quality of work life and organizational commitment to nurses at Unand Hospital in 2023. This research was carried out at Unand Hospital throughout 2024 using a mix methods research method . This method was used. This was carried out with the aim of knowing the frequency distribution of the relationship between employee engagement, quality of work life and organizational commitment to the turnover intention of nurses at Unand Hospital and being able to explain this further through informant interviews. The research results then showed that there was a negative relationship between the employee engagement of nurses at Unand Hospital, the lower the level of turnover intention of nurses at Unand Hospital, the quality of work-life of nurses had a negative and significant effect on the turnover intention of nurses at Unand Hospital and organizational commitment had a negative and significant effect on the turnover intention of nurses at Unand Hospital. significant impact on the turnover intention of nurses at Unand Hospital. So this shows that if the implementation of employee engagement , quality of work life and organizational commitment is increasingly improved, the level of turnover intention that occurs will decrease. This was also expressed by nurses who stated their low level of turnover intention. while working at Unand Hospital due to the comfort of work, harmony with co-workers and greater career and study opportunities at Unand Hospital. So it is hoped that Unand Hospital will maintain the quality and quantity of its human resources by increasing employee engagement, quality of work life and organizational commitment so that it has an impact on the quality of service delivery to the public.